Implementasi Metode Mindmapp Dalam Pembelajaran Ilmu Nahwu Siswi XI Program Keagamaan MAN 1 Probolinggo - Firdausiyah, Zahroh; Wijaya, Muallim (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
In this journal the authors conduct research with the aim of knowing 1) the effectiveness of mindmapp media in studying nahwu science. 2) Mind maps can attract students' attention in learning. 3) Mindmapp is a solution in understanding nahwu science. Data were collected by observation and interviews with 5 students of the Religious Program using descriptive and qualitative techniques. The subjects and objects of this study were students of class Xl in the Man 1 Probolinggo Religious Program. The results of research in the field are as follows: 1) Mindmapp media makes it easier for some Man Pk students to understand nahwu material which is difficult to discuss. 2) The existence of Mindmapp increases the creativity of students in creating and processing data. 3) The existence of a mind map makes it easier for students to repeat material and memorize.